PENERAPAN SISTEM INFORMASI PEMETAAN DAN PELAPORAN KERUSAKAN INFRASTRUKTUR DESA BERBASIS WEB UNTUK MENDUKUNG PERENCANAAN PEMBANGUNAN - Sari Utama Dewi; Fery Hendi Jaya; Eko Aziz Apriadi (ABDI AKOMMEDIA : JURNAL PENGABDIAN MASYARAKAT, 2026)
The limited availability of spatial databases and standardized infrastructure-damage reporting mechanisms often forces village governments to prioritize development using fragmented, inconsistent, and difficult-to-verify information. This community service program implemented a web-based information system integrating asset mapping, damage reporting, photographic evidence, geographic coordinates, verification, and repair prioritization. The main activity was conducted in Kurungan Nyawa Village, Gedong Tataan District, Pesawaran Regency, Lampung, on 1 March 2026 from 10:00 a.m. to 12:00 p.m. The method included needs assessment, database preparation, system demonstration, reporting practice, mentoring, pretest-posttest, and usability evaluation. The system managed 126 infrastructure objects and 47 damage reports covering roads, drainage, bridges or culverts, water facilities, and public service buildings. The average competency score of 24 participants increased from 41.25 to 83.00, while task-completion success reached 91.7%. The outputs consisted of a responsive WebGIS application, a spatial database, operational guidelines, role-based accounts, and an infrastructure-treatment priority matrix. The system accelerated data consolidation, improved report traceability, and provided spatial evidence to support village development-planning forums.